ANALISIS KINERJA UPTD BLK DINAS TENAGA KERJA KABUPATEN SEMARANG DALAM MENJALANKAN PELATIHAN BERBASIS KOMPETENSI - Arini, Arini; Maesaroh, Maesaroh (Journal of Public Policy and Management Review, 2019)
Semarang regency labor issues today is the lack of quality labor that it has. BLK Semarang Regency is a technical executive unit of labor office which has task in the area of labor training. This research aims find out UPTD BLK’s performance in running the competency based training. The method used in the research is the qualitative descriptive type. Indicators used to assess performance are productivity, service quality, responsiveness, responsibility, and accountability. The results showed that the performance of the UPTD BLK of the Labor Office in running a competency based training program was not optimal, there were still some problems with indicators of productivity, service quality, responsiveness, and accountability,only indicators of responbility that had gone well. The factors that inhibit the performance of UPTD BLK covering human resources and infrastructure. Related to effort of improving UPTD BLK’s performance in running the competency based training, researcher’s recommendations are to add the amount of classrom, to establish cooperation with company to distribute BLK’s graduates, to complete facilities in dormitory, to socialize thoroughly in Semarang district, and to update information displayed on the website.